Smart stewardship for nonprofits : making the right decision in good times and bad - Brinckerhoff, Peter C., 1952- (Hoboken, N.J. : John Wiley & Sons, 2012)
'A practical guide to effective decision-making frameworks and tools for nonprofits that ensure successful stewardship. The basic tenets of decision making for nonprofits are similar, whether you're growing, shrinking, or trying to think your way out of a box. Smart Stewardship for Nonprofits provides the tools to make the best stewardship decisions in these varied, but common, situations. Coverage includes the keys to smart stewardship for your nonprofit, the smart stewardship decision tree, understanding capability and capacity, making innovation the norm, understanding the true cost of growth, going to scale, and smart stewardship in bad times. Features tools to make the best stewardship decisions in every kind of situation Written for executive directors of nonprofit organizations, nonprofit board members, CPAs, and other financial counsel for nonprofits, development directors Provides a website hosting a variety of online tools and materials. Also by Peter Brinckerhoff: Mission-Based Marketing, Mission-Based Management, Social Entrepreneurship, and Faith-Based Management. With innovative organizational change initiatives to foster new growth and effectiveness, Smart Stewardship for Nonprofits offers your nonprofit the critical guidance it needs to get there'--
Includes bibliographical references and index.
Keywords: Nonprofit organizations; Decision making; Problem solving